The impact of charitable work on self-preservation and money - Hussain , Zainab; Abdullah, Basma (Islamic Sciences Journal, 2023)
Praise be to Allah, the owner of benevolence and generosity, the venerable giving, the possessor of blessings, and prayers and peace be upon my role model, the best of all creation, Muhammad (may Allah bless him and grant him peace). The Islamic Sharia has given great attention to every means that leads to the preservation of necessities in terms of existence and non-existence. It has also paid great attention to the most powerful means that affect the preservation of necessities, which is (charitable work). All of this is that charitable work is very important and should be done seriously and with great enthusiasm, and the idea of charitable work is rooted in Islamic law in the Holy Qur’an and the honorable Sunnah of the Prophet, and among the most important things that help one to do charitable work: A - Religious motive. b- Adapting to the morals of our Prophet Muhammad (may Allah bless him and grant him peace).